Narrow genetic base of Indian litchi (Litchi chinensis) cultivars based on molecular markers - BAJPAI, ANJU; MUTHUKUMAR, M; SINGH, AWTAR; NATH, VISHAL; RAVISHANKAR, H (The Indian Journal of Agricultural Sciences, 2016)
Litchi (Litchi chinensis Sonn.) is an introduced crop in India and has limited genetic variability characterized by differences in flushing pattern, leaf, panicle and fruit traits. Molecular markers were employed to expose the genetic diversity of 20 litchi cultivars from the Indian peninsula and facilitate documentation of the native germplasm diversity. Efficiency of individual primers was evaluated on the basis of average band informativeness and resolving power, where random oligonucleotide markers OPA-5 and OPA-3 scored best. Among tested microsatellite markers, ISSR 01 and 13 had high values for primer efficiency and these were found to supplement simple sequence repeats for generation of cultivar barcode and clustering analyses. Efficiency of microsatellites (Simple Sequence Repeats and Inter Simple Sequence Repeats) was established by high values for polymorphism (0.691), diversity index (0.264), effective multiplex ratio (48.8470) and marker index (12.896), thus reiterating its potential as for developing barcodes for cultivar identification and conservation. Phylogenetic analysis based on RAPD and microsatellites revealed clustering of the cultivars into four major groups, although within a very narrow range (0.63 - 0.90) of similarity, viz. Seedless (i.e. Bedana), Mandarji, Shahi and China groups. The clustering followed grouping based on fruit morphology, leaf and panicle attributes disagreeing with earlier views regarding incongruity of clustering pattern with morphological, ecological and climatic adaptations. Discrimination of cultivars like Dehrarose and Dehradun, being often labeled as synonyms, was also done. Interestingly high polymorphism and low gene diversity have been exposed by molecular markers, commenting on narrow genetic background of litchi cultivars from India.